Queerizzare le epistemologie: Materie ibride e disidentificazione nella scena performativa - Caleo, Ilenia (Mimesis Journal, 2023)
How is the performance intertwined with the transformations and crises of the present? How do the live arts make-world? And vice versa, can the forms of life and subjectivities emerging from ongoing conflicts provide us new glimpses into performative practices? From a queer feminist perspective, the paper maps some incandescences and zones of commonality between aesthetic forms and life forms – both understood as modes of creation, of invention. Contemporary live arts destabilize systems of perception that are considered stable, questioning the status of corporeality, the boundaries between human/more-than-human, the ways of composing the world, the logics of the sensible, opening up to new epistemologies and perverse archives. Hybrid, promiscuous bodies. Phantasmatic bodies, spectral frequencies, hauntings. Impossible, illegible, unthinkable bodies. Mixed, impure lives, meteorological dramaturgies. Mixtures with the animal, the machine, the inanimate matter. In these processes of research and interstices in-between, the performance does not represent but creates new corporealities, sequences of movements, scores, other possible anatomies.